Development and Testing of Test Rig for Reliability of Automobile Differential - Aifen Xu; Jumin Jia; Ze'nan Tao; Chao Yang (Jixie chuandong)
Based on the reliability requirements of the differential，the hardware and software structures of the test rig are designed. A rig for differential test is developed， and reliability tests under two conditions of the high rate and low torque and the low rate and high torque are carried out according to the industry standards. The test result indicates that the test operation state is consistent with the test requirements， and the test results are accurate and reliable， fully meeting the test requirements of differential reliability. It provides practical guidance for the standardized conduction of the reliability testing of automobile differential.